The Role of Management Styles in the Systematic Development of the Digital Economy - Karjavovich, Karjavov Zayniddin; Norboevich, Jumanov Sherzod; Zokirovich, Saydirasulov Alisher (Research Parks Publishers, 2023)
This article highlights the role and importance of management methods in the systematic development of the digital economy.